Implementation of Character Education in Strengthening Indonesia Santri’s National Spirit - Sahabuddin; Sileuw, Marwan; Umkabu, Talabudin (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
Character education is important in strengthening the national spirit (nationalism) of Santri in pesantren. However, studies that discuss character education only focus on the conceptual level or understanding. Hence, the form of application and implications of character education in increasing the spirit of nationalism among Indonesian Santri tend to be neglected. By focusing on the form and implications of the implementation of character education among Indonesian Santri, this study chose to use a descriptive qualitative approach based on observation, documentation, and interviews with coaches and Santri. The findings in this study successfully revealed that character education implemented by training students to use the Indonesian language properly, familiarizing students with Indonesian products, and involving students in reflection and appreciation activities on the struggle of heroes not only succeeded in increasing the spirit of nationalism or nationalism but also fostered empathy for differences and improved the academic competence of students. This study recommends future research to explore the effectiveness of Indonesian character education strategies in enhancing the spirit of nationalism and implementing the program in formal and non-formal education environments.